Knowledge and Perception of Religious Leaders on Premarital Genetic Counseling for Sickle Cell Disease in Kano, Northern Nigeria - Galadanci, Aisha; Ibrahim, Umma; Farouk, Zubaida; Abdulqadir, Ibrahim; Caroll, Yvonne; Ding, Juan; Kang, Guolin; Idris, Ibrahim; Musa, Baba; Mukaddas, Aisha; Sani, Bilya; Hussaini, Nafiu; et al. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Nigeria has the highest burden of sickle cell disease in the world. Premarital counseling (PMC) programs to reduce the burden of hemoglobinopathies have been successfully implemented in Muslim predominant countries with similar religious and cultural practices to northern Nigeria. Religious leaders have a significant role to play in the success of PMC in northern Nigeria.Aims: To assess the knowledge and perception of premarital genetic counseling for sickle cell disease (SCD) among religious leaders in a culturally and religiously sensitive environment.Settings and Design: A cross-sectional (pre and post) study was conducted during the premarital screening workshop for SCD on July 20th, 2019, at Bayero University Kano, northwest Nigeria.Materials and Methods: Convenient sampling method was used to identify and invite 126 Islamic clerics through the CICID (Centre for Islamic Civilization and Interfaith Dialogue) at Bayero University Kano, to a premarital screening workshop for SCD. Self-administered semi-structured pre-and posttest questionnaires were used to collect data from the participants. Aminu Kano Teaching Hospital Human Health Research and Ethics Committee approved this study.Statistical Analysis Used: Statistical analyses were performed with R version 4.0.2. The data were summarized using descriptive statistics and presented as mean ± standard deviation (SD), median and interquartile range (IQR), and percentages as appropriate. Wilcoxon test for score comparison of pre-and posttest was used with a significance level of 0.05.Results: A total of 97 religious' leaders with a mean age ± SD of 44.7 ± 12.7 completed both pre-and posttests. The male-to-female ratio was 5:1. Participants gave more accurate responses to questions during the posttest period than during the pretest; knowledge of the sign of SCD (Proportion of False Discoveries Rate (pFDR) =0.005), knowledge for the complications of SCD (pFDR =
Keywords: Islamic clerics; knowledge and perception; premarital counseling; religious leaders; SCD